2016
DOI: 10.1371/journal.pone.0158873
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Impairs Insulin Signaling in the Glomerulus: An In Vitro and Ex Vivo Approach

Abstract: ObjectiveChronic hyperglycaemia, as seen in type II diabetes, results in both morphological and functional impairments of podocytes in the kidney. We investigated the effects of high glucose (HG) on the insulin signaling pathway, focusing on cell survival and apoptotic markers, in immortalized human glomerular cells (HGEC; podocytes) and isolated glomeruli from healthy rats.Methods and FindingsHGEC and isolated glomeruli were cultured for various time intervals under HG concentrations in the presence or absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 68 publications
2
22
0
Order By: Relevance
“…Specifically, CD2AP was reported to interact with both nephrin and PI3K in vivo, stimulating anti-apoptotic Akt signalling in podocytes [12]. Chronic hyperglycaemia disrupts signal transduction pathways involved in glomerular survival [36]. Our previous work [37], as well as work by others [38] demonstrated a decrease of glomerular nephrin expression as an early event in hyperglycaemic conditions.…”
Section: Discussionmentioning
confidence: 87%
“…Specifically, CD2AP was reported to interact with both nephrin and PI3K in vivo, stimulating anti-apoptotic Akt signalling in podocytes [12]. Chronic hyperglycaemia disrupts signal transduction pathways involved in glomerular survival [36]. Our previous work [37], as well as work by others [38] demonstrated a decrease of glomerular nephrin expression as an early event in hyperglycaemic conditions.…”
Section: Discussionmentioning
confidence: 87%
“…These are the pathways of nuclear transcription factor receptors: peroxisome proliferator-activated receptor (PPAR), liver X receptor (LXR) and retinoid X receptor (RXR) and have a role in cellular metabolism. The inhibition of PPAR signalling in PCTS might be caused by the high concentration of glucose in the culture media (25 mM), as similar concentrations of glucose were reported to inhibit PPAR (Roduit et al 2000;Cheng et al 2013;Domínguez-Avila et al 2016) and to lead to several transcriptional changes in different organs (Katsoulieris et al 2016;Boztepe and Gulec 2018). However, further functional experiments are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, earlier reports demonstrated that FOXO3a activation is related to podocyte apoptosis under high glucose conditions and in aging kidneys between which oxidative stress is a common feature. 40,41 These findings suggest that FOXO3a is more likely to induce podocyte apoptosis under oxidative stress conditions. However, some studies show that FOXO3a plays a pro-survival role in chronic tubular injury by activating antioxidant genes or autophagy-related genes, 25,26,42 but we did not observe this protective role of FOXO3a in AOPPs-treated podocyte.…”
Section: Discussionmentioning
confidence: 88%